2015
DOI: 10.4238/2015.may.4.20
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase variants associated with risk and clinical outcome of esophageal cancer

Abstract: ABSTRACT. We conducted a case-control study to investigate the role of matrix metalloproteinase (MMP) 2, MMP3, and MMP9 single nucleotide polymorphisms on susceptibility to esophageal squamous cell carcinoma (ESCC) in a Chinese population, and their association with environmental factors. A total of 226 patients with ESCC, and 226 age-and gender-matched healthy controls were enrolled in this study. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis was carried out on MMP2 -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
0
15
0
2
Order By: Relevance
“…[ 16 , 17 ] Some SNPs in promoter region play an important role in disease development. [ 18 , 19 ] Moreover, the relationship between variants in MMP2 and MMP9 genes and RSA risk has been reported in several published articles. A case–control study carried out among Slovenian population demonstrated that MMP2 and MMP9 polymorphisms were significantly associated with RSA risk.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 , 17 ] Some SNPs in promoter region play an important role in disease development. [ 18 , 19 ] Moreover, the relationship between variants in MMP2 and MMP9 genes and RSA risk has been reported in several published articles. A case–control study carried out among Slovenian population demonstrated that MMP2 and MMP9 polymorphisms were significantly associated with RSA risk.…”
Section: Introductionmentioning
confidence: 99%
“…127 Zhang et al investigated MMP2, -3, and -9 single-nucleotide polymorphisms in esophageal SCC. 128 The authors suggested that MMP2 -1306TT and MMP9 -1562CC single-nucleotide polymorphisms correlated with increased esophageal SCC risk and significantly high death odds. 128 In a study by Virós et al, 129 the prognostic value of MMP2-and -9-expression levels in patients with HNSCC following treatment with radiotherapy or chemotherapy was analyzed by multivariate analysis.…”
Section: Mmps As Tumor Biomarkersmentioning
confidence: 99%
“…It is revealed that TT genotype reduces the incidence of esophageal squamous cell carcinoma (ESCC). [ 20 ] Low et al [ 21 ] showed that this SNP marginally related to intracranial aneurysm (IA) in a Japanese population. It also reduces the rheumatoid arthritis (RA) risk in a Chinese population.…”
Section: Discussionmentioning
confidence: 99%